Elements of style. - Cardin, Marlene McGinnis; Charney, Nicolas H. (Videofashion, 2008)
"Visit Noho with designer Antonio Berardi. Examine vintage finds with Gavin Douglas in Camden Passage. Tour hot Johannesburg shops with Black Coffee. Explore aint Germain with Catherine Malandrino."--Publisher website.